Skriftemålet i Danmark : Fra senmiddelalder og frem til kirkeordinansen 1539 - Bruun, Carsten (Kirkehistoriske Samlinger, 1989)
The Reformation represents an enormous ideological change in Danish churchhistory. But at least in one area the practical guidelines more or less remained unchanged after the Reformation, namely the confession. This article deals with the development of confession from the late Middle Ages to the Lutheran Church Ordinance 1537/39. The Roman Catholic Church emphasized that man, after confession and after execution of the - from the minister - imposed penalty, was free of guilt. The people behind the Reformation rejected the idea of innocence through good deeds. Innocence was, to them, a matter of faith. This attitude did not mean, that they rejected the institution of confession altogether. In the period from 1526, when the reformatory ideas first occurred in Denmark, till the Church Ordinance 1537/39 two branches of reformatory preachers were present in Denmark. The South-German inspired branch, represented by Zwinglis ideology, most radically settled with the institution of Catholic confession. The preachers belonging to this branch believed in the direct confession between man and God, in which absolution was given by the death of Christ. The Lutheran branch also, ideologically, rejected the Catholic confession - hereby they agreed with Zwingli. But this branch also believed in an institution of confession - with the church as a connecting link between man and God. But opposed to the Catholic confession, the Lutheran version was a question of consciousness of sin and faith. In spite of the different perception of the confession, the entire practice of the Lutheran confession was very much alike the Catholic version. By the Reformation in 1536 the Lutheran branch had taken over the theological dominance. The Church Ordinance finally completed in 1539, was therefor the ideological work of the Lutheran preachers. The main characteristik development of the confession from the Roman Catholic to the Lutheran-Evangelical church is, that the revolutionary new formulation in the understanding of christanity, does not mean a similar change in the administration of the institution.